EFFECTIVENESS OF ALBENDAZOLE AGAINST NEMATODES IN BALI CATTLE OF SUKA DHARMA FARMER’S GROUP AT BATURITI, TABANAN - Al-Aliyya, Raisis Farah Dzakiyyah; Apsari, Ida Ayu Pasti; Kencana, Gusti Ayu Yuniati (Buletin Veteriner Udayana; Vol. 14 No. 5 October 2022, 2022)
This study aims to determine the effectiveness of albendazole against nematodes in bali cattle of farmer group Suka Dharma in Baturiti, Tabanan. Samples consists of 16 bali cattles which were divided into two groups, namely the control group that was not given albendazole therapy and the treatment group which was given albendazole at a dosage of 7,5 mg/kg of cattle’s weight orally. Faeces sampling was carried out on days 0, 7, 14, 21, and 28 post albendazole treatment. Samples were examined using the Wisconsin floating method to provide number of nematode eggs per gram faeces. Faecal Egg Counts Reduction was calculated to evaluate albendazole efficacy. The data obtained were further analyzed by Wilcoxon statistical tests. FECR values indicate that nematode worm eggs in bali cattle from the treatment group decreased by 91.55% on the 28 th day post albendazole administration. Analysis by Wilcoxon test showed significant differences (P<0.05) between the number of nematode worm eggs in bali cattle before albendazole treatment and post albendazole treatment. It can be concluded that albendazole is effective against nematode worm infection in bali cattle of the Farmers' Group Suka Dharma, Baturiti, Tabanan.